The Pasig river as an integrative design element in Metro Manila - De la Cruz-Luis, Prosperidad 1942- (1975)
Human settlement patterns have been observed to gravitate towards water. Water, however, is most vulnerable to overuse. The tendency of people towards permanent occupance of water edges have resulted to polluted waters and mutilated banks. The Pasig River, the case for this study, is a river with numerous problems: a) the "no man's land" of public easements which the statutes of the land have ruled to have the original intention of allowing for the full and wide-spread utilization of the water is illegally occupied by squatters who destroy its banks and pollute its waters; b) the industries line more than half its entire length and together contribute to the disintegration of the river's water quality; c) Metropolitan Manila, which the river traverses suffers from heavy flood losses for having persisted with flood plain land uses that are not compatible with occurence of floods; d) though the river is physically at the center of Metro Manila, it is not part of people's images in general because it is not accessible for most of its length; e) the river is enmeshed in the unique political and administrative set-up of the country - efforts at development are unintegrated, fragmented and oftentimes stalemated by insistence for autonomy by the local governments. The general objective of this study is to evolve a development concept for the integration of waterways into community design, using the Pasig River as a case study. The major proposal arrived at is for the entire length of the river to be developed basically as a venue for linear recreation with great recreational nodes occuring at the intersection of the Pasig River with the six circumferential routes of Metropolitan Manila. This potential of the river is strengthned by five factors: a) water space as open space offers leisure potentials without taking away from use expensive land of equal area; b) the linear characteristic of the river offers a wide and at the same time distributed accessibility to leisure-seeking citizens; c) statutes of the land offer a convenient starting point of development in the minimum three meter easements reserved as public property; d) a linear recreational open strip along the river is a defense against flood damages; and e) previous experiences show that developing and opening the river elicit positive responses and a sense of responsibility in people for the upkeep and maintenance of the facilities. Since the river is pent in on both sides of existing land uses was done. The study supported the workability of the proposed linear recreational use of the river. It showed that in general, no land use is totally incompatible with recreational use.